PENCEGAHAN KEKERASAN DI TEMPAT PENITIPAN ANAK (STUDI KASUS: DAYCARE X, Y, DAN Z DI KOTA PEKANBARU TAHUN 2024) - Ginting, Emya Elitna Ananta; Usmita , Fakhri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Daycare helps working parents by providing childcare and education services. However, daycare can become places of violence if they are not supervised. Child protection needs to be implemented by the relevant agencies, supported by caregivers, and accompanied by training. Parents also need to be educated because they are responsible for fulfilling children's rights. This study uses a qualitative research method. In qualitative research, the researcher acts as a data collection tool. This study focuses on the phenomenon of violence in childcare centers through case studies, involving observation and interviews. With this approach, the researcher can explore the factors influencing violence, the prevention strategies implemented, and the contribution of childcare centers to child protection. Based on Routine Activities Theory, preventing violence against children in daycare will be most effective if it can prevent the perpetrator, target, and lack of supervision from occurring simultaneously. These efforts include training and education to reduce the potential for perpetrators, empathetic and risk-aware caregiving to protect children as targets, and strengthening supervision systems involving caregivers, institutions, relevant agencies, and active parental involvement. Preventing violence against children in daycare requires synergy between strong regulations, continuous supervision, empathetic and professional caregivers, and active parental involvement. To achieve a holistic and sustainable child protection system, it is necessary to strengthen formal structures, continuously enhance caregiver capacity, and optimize the role of government agencies and cross-sectoral institutions in monitoring and training.